Endosperm culture of Jatropha curcas L. - Pasitvilaiturm,M. (Chiang Mai University, 2015)
Endosperm culture of Jatropha curcas L. or physic nut is an interesting method, but no previous studies have been reported. Endosperm explants were cultured on Murashige and Skoog media supplemented with 30 g/L sucrose and various concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D), 1ñnaphthaleneacetic acid (NAA) and indole-3-butyric acid (IBA) i.e. 0, 5 and 10 μM, and kept under darkness for 45 days. The results showed that the highest percentage of callus induction was found on the medium supplemented with 10 μM NAA (100%) followed by 10 μM 2,4-D (92%) and 10 μM IBA (86%). However, no callus was observed in the control medium and medium supplemented with 5 μM 2,4-D, NAA and IBA. In addition, the largest compact yellow callus was found on the medium with 10 μM 2,4-D and NAA while small yellowish callus was found on the medium with 10 μM IBA. In further study, friable callus derived from endosperm were used for suspension culture. Growth rate of suspended cells and percentage of oil content during growth period were measured. The results revealed that endosperm cells could grow and could produce oil. The suspended cells grow rapidly during 10-15 days of culture and gave the maximum percentage of oil content 16.08% (w/v) at 15 days of culture then decreased to 4% on the last day of culture (40 days).